Respostas
respondido por:
0
Método da adição;
2x - 2y = 12
- x + 2y = - 1,,,,,,,,,,(somando as equações)
=> x = 12 - 1.......=> x = 11
- x + 2y = - 1
2y = - 1 + x
2y = - 1 + 11
2y = 10....=> y = 10 : 2.....=>... y = 5
Solução:....S = {(x, y)} = {(11, 5)}
respondido por:
0
Mayra segue o mesmo formato das outras equações
Faz-se a soma
2x-x-2y+2y=12-1
X=11 logo
-X+2y= -1
-11+2y= -1
2y= 11 - 1
2y= 10
Y=5
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás